1986
DOI: 10.1190/1.1442052
|View full text |Cite
|
Sign up to set email alerts
|

Self‐potential variations with time and their relation to hydrogeologic and meteorological parameters

Abstract: A systematic investigation of self potentials (SP) shows that they vary considerably with time. To study the influencing parameters, repeated measurements were conducted every 14 days over a period of a year and a half along fixed profiles which extended over different lithological units. An analysis of the recorded SP suggests decomposition into three components of different wavelengths. Variations of the SP with wavelengths in the 0.1–1 m range and amplitudes of up to 150 mV are thought to be induced by vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…In the absence of a hydrothermal system, fluid flow will be restricted to the mostly vertical flow of vadose water towards a water table. The linear reverse relationship between SP and altitude commonly observed on the flanks of volcanoes is thought to be related to an increase in thickness of the vadose zone with altitude (Zablocki 1978;Schiavone and Quarto 1984;Ernstson and Scherer 1986;Jackson and Kauahikaua 1987;Aubert and Atangana 1996;Aubert et al 1990Aubert et al , 1991Aubert et al , 1993. At Kilauea volcano, Jackson and Kauahikaua (1987) showed that this relationship can be used to detect water table depth.…”
Section: Sources Of T Sp and Co 2 Anomaliesmentioning
confidence: 99%
“…In the absence of a hydrothermal system, fluid flow will be restricted to the mostly vertical flow of vadose water towards a water table. The linear reverse relationship between SP and altitude commonly observed on the flanks of volcanoes is thought to be related to an increase in thickness of the vadose zone with altitude (Zablocki 1978;Schiavone and Quarto 1984;Ernstson and Scherer 1986;Jackson and Kauahikaua 1987;Aubert and Atangana 1996;Aubert et al 1990Aubert et al , 1991Aubert et al , 1993. At Kilauea volcano, Jackson and Kauahikaua (1987) showed that this relationship can be used to detect water table depth.…”
Section: Sources Of T Sp and Co 2 Anomaliesmentioning
confidence: 99%
“…As the salt was removed, the potential sampled by the electrode through the volume average of the conductive salted zone was changing accordingly. The natural soil has indeed an heterogeneous electrical structure, and SP varies on a few cm distance by a few mV (Ernstson and Scherer, 1986;Clerc et al, 1997).…”
Section: General Observations For Dipoles In the Soilmentioning
confidence: 99%
“…The fabrication is still a largely undocumented craft and there seems to be no consensus on the performances of the various types of electrodes (Junge, 1990;Larsen, 1992;Erkul and Muller, 1996). Although some systematic studies of the time variations of SP have been undertaken (Ernstson and Scherer, 1986), many phenomena related to the electrochemical contact with the external medium are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This anomaly is interpreted as resulting from shallow, gravitational groundwater flow in the nearsubsurface from the crest to the toe, similar to the "negative summit" phenomenon commonly observed in SP surveys over steep terrain (e.g. Corwin, 1989;Corwin and Hoover, 1979;Ernstson and Scherer, 1986). Interestingly, however, the most negative SP does not occur at the crest of the dam (though measurements are admittedly sparse in this area), an observation that is explored in Section 5.1 of the Discussion.…”
Section: Self-potentialmentioning
confidence: 58%